2021
DOI: 10.1515/jpm-2020-0525
|View full text |Cite
|
Sign up to set email alerts
|

Maternal oxytocin administration modulates gene expression in the brains of perinatal mice

Abstract: Objectives Oxytocin (OXT) is widely used to facilitate labor. However, little is known about the effects of perinatal OXT exposure on the developing brain. We investigated the effects of maternal OXT administration on gene expression in perinatal mouse brains. Methods Pregnant C57BL/6 mice were treated with saline or OXT at term (n=6–7/group). Dams and pups were euthanized on gestational day (GD) 18.5 after delivery by C-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Consistent with the effect of prolonged Oxt exposure on the Oxtr, 32 , 33 , 39 we noted a decrease in Oxtr gene and protein expression in the developing brain. Our observations are largely consistent with sex-specific Oxtr downregulation observed at GD18.5 and P9 after perinatal Oxt administration reported by Hsieh et al., 47 but at odds with those of Hirayama et al. 45 This inconsistency can be partly explained by differences in the mode of administration (intravenous vs. subcutaneous), the duration of Oxt exposure, and whether or not Oxt administration resulted in birth.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with the effect of prolonged Oxt exposure on the Oxtr, 32 , 33 , 39 we noted a decrease in Oxtr gene and protein expression in the developing brain. Our observations are largely consistent with sex-specific Oxtr downregulation observed at GD18.5 and P9 after perinatal Oxt administration reported by Hsieh et al., 47 but at odds with those of Hirayama et al. 45 This inconsistency can be partly explained by differences in the mode of administration (intravenous vs. subcutaneous), the duration of Oxt exposure, and whether or not Oxt administration resulted in birth.…”
Section: Discussionsupporting
confidence: 91%
“…Our work adds significantly to the growing body of animal research suggesting that perinatal exposure to Oxt could be consequential for the offspring. 31 , 45 , 46 , 47 , 48 Our model, however, is distinctive because: (i) Oxt was administered to induce and augment labor making it contextually relevant to modern obstetric practice, (ii) the biological effects of Oxt on cyclical uterine contractility were comprehensively studied and validated previously, 38 (iii) measures of maternal-neonatal wellbeing after Oxt exposure were assayed and confirmed, and (iv) the sophisticated social behavioral repertoire of the offspring from a genetically robust, outbred rat strain was fully leveraged to enable thorough characterization of ASD-specific neurobehavioral changes. By simulating management of human labor with Oxt infusion and ensuring maternal-neonatal wellbeing, results from our work are likely to be translationally relevant than currently existing preclinical models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the above studies are informative, they do not simulate labor induction because in these studies exposure to oxytocin occurred after birth. One study simulating labor induction found that maternal oxytocin treatment in mice resulted in widespread differential gene expression in embryonic brains, with enrichment for genes involved in protein localization within the cell (Hsieh et al., 2022). This same group, however, found no differential gene expression in the brains of mice born to saline‐ and oxytocin‐treated dams at postnatal day 9 (Hsieh et al., 2022).…”
Section: Introductionmentioning
confidence: 99%